Analisis Literatur: Pengaruh Budaya Organisasi Terhadap Penyelesaian Konflik Mahasiswa UPI - Avvyat Anantya; Cut Siti Balqis; Rika Sartika; Bunyamin Maftuh (Laboratorium Sosiologi, Program Studi Sosiologi, Fakultas Ilmu Sosial, Universitas Nahdlatul Ulama Indonesia (UNUSIA) Jakarta, 2024)
This article examines the influence of organizational culture on conflict resolution among students at the Universitas Pendidikan Indonesia. Using a literature review method, the research identifies various elements of organizational culture, including values, norms, and communication patterns that play a role in student interactions. The analysis shows that a positive and inclusive organizational culture not only facilitates constructive conflict resolution but also enhances collaboration and trust among students. The study also finds that a deep understanding of organizational culture can help students manage differences of opinion and create a harmonious environment. Consequently, this research provides insights for university policymakers to design programs and activities that strengthen an organizational culture supportive of conflict resolution. The findings are expected to serve as a reference for fostering a more productive and respectful academic atmosphere, additionally, it is expected that individuals will be able to understand diverse organizational cultures to effectively resolve potential or existing conflicts.